DISCREPANCY OF MCMP DERIVED FROM EXPERIMENTS AND PREDICTION MODELS OF SOME INDONESIAN OIL FIELDS - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2014)
Most of oil fi elds in Indonesian have been categorized as mature fi elds, since the primary stages of theoil production nearly fi nished. Therefore EOR technology is the only option to rejuvenate those old oil fi eldsto increase the oil recovery. CO2 miscible fl ooding, one of the proven EOR technology, can be implementedin some Indonesia oil fi elds if they fulfi ll the screening criteria for CO2 injection. Laboratory works initiallyshould be carried out to determine some parameters for calibrating the reservoir simulation program. Themost important parameter is MCMP (multiple contact miscibility pressure), this pressure level can be usedto determine the displacement effi ciency of the CO2 injection. Above the MCMP will be more effi cientcompare to below MCMP injection pressure. MCMP is normally can be obtained in the lab by a Slim tubeapparatus. In case there are no oil and gas sample available, some correlations based on the empiricalfi eld data are also available in the literature as well as EOS (equation of state) for predicting MCMP. Somereservoir fl uids MCMP have been evaluated using those three methods. Then, discrepancies were calculatedto compare the results of Slim tube tests, correlations and EOS calculation. Four correlations such as NPC(National Petroleum Council), Cronquist et al, Yellig-Metcalfe, Holm-Yosendal and one EOS modeling ofPeng-Robinson (1978) have been proposed to predict the MCMP fourteen reservoirs. Moreover, those MCMPwere also run using Slim tube. Holm-Yosendal correlation has nine reservoirs and secondly Yellig-Metcalfemethod possesses six reservoirs with discrepancy below 10% compare to MCMP obtained from Slim Tubetests. While the other methods are not appropriate as well as Peng-Robinson EOS modeling without anylaboratory data for calibration.